The expandable metal stent for tracheal obstruction. Issue 5 (May 1995) - Boothroyd, A E; Edwards, R; Petros, A J; Franks, R
Abstract : A 10 month old boy with stridor persisting from birth was found to have tracheal narrowing secondary to myofibromatosis of the tracheal wall. An expandable metal stent was positioned across the tracheal stenosis with immediate clinical improvement. There were no complications relating to stent insertion. The child remained clinically asymptomatic and repeat bronchoscopy at nine months' follow up showed that the stent had become completely endothelialised with no evidence of granuloma formation.